The Effect Of Techno-Stressors On Work Life Balance With Self-Efficacy Moderation And Emotional Exhaustion Mediation On Digital Transformation Study at PERUMDA Air Minum Tirta Sewakadarma - Yulia Putri, Theresa Ventyana; Aprillia Rahayu Putri, Ni Putu Tanya; Prasetyaningtyas, Sekar Wulan (ITB AAS Indonesia Surakarta, 2024)
This study aims to analyze the effect of Techno-Stressors on work life balance, the effect of Techno-Stressors on work life balance through Self-efficacy as a moderating variable and the effect of Emotional Exhaustion is able to mediate Self-efficacy which moderates the effect of Techno-Stressors on Work life balance of Employees on Digital Transformation PERUMDA Air Minum Tirta Sewakadarma. This type of research is explanatory quantitative. The research subjects were employees of PERUMDA Tirta Sewakadarma Drinking Water in Denpasar City consisting of technical experts and administrative and financial experts who experienced pre- and post-digital transformation. The population is all employees of PERUMDA Tirta Sewakadarma Drinking Water, totaling 312 people. The research sample amounted to 100 people after rounding. Data collection methods are interviews and questionnaires. This study uses Partial Least Square Structural Equation Modeling (PLS-SEM) analysis. The results show that Techno-Stressors have a significant effect on work life balance, Self-efficacy has no effect in moderating Techno-Stressors on work life balance, and Emotional Exhaustion has a significant effect in mediating the effect of Techno-Stressors on employee work life balance on digital transformation at PERUMDA Air Minum Tirta Sewakadarma.